2011
DOI: 10.3892/or.2011.1270
|View full text |Cite
|
Sign up to set email alerts
|

Rare MDM4 gene amplification in colorectal cancer: The principle of a mutually exclusive relationship between MDM alteration and TP53 inactivation is not applicable

Abstract: Abstract. MDM4, a homolog of MDM2, is considered a key negative regulator of p53. Gene amplification of MDM4 has been identified in a variety of tumors. MDM2 or MDM4 gene amplification is only associated with the wild-type TP53 gene in retinoblastomas, thus the amplification of the two genes is mutually exclusive. Previously, we demonstrated that MDM2 amplification and TP53 alteration were not mutually exclusive in colorectal cancer, and we identified a subset of colorectal cancer patients without alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…On the other hand, MDM2 amplification can induce resistance to ICI by reducing T-cell activation in malignancies (25,26). Although none of these molecular alterations was found in CRC with HPD, which may be related to the 27) demonstrated that the principle of rare MDM4 amplification in CRC is unclear, which is different from the mechanism of a mutually exclusive relationship between MDM2 alteration and TP53 inactivation (27). More importantly, our case carries MDM4 and DNMT3A co-mutation, which have not been reported in CRC by the Cbioportal Database.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, MDM2 amplification can induce resistance to ICI by reducing T-cell activation in malignancies (25,26). Although none of these molecular alterations was found in CRC with HPD, which may be related to the 27) demonstrated that the principle of rare MDM4 amplification in CRC is unclear, which is different from the mechanism of a mutually exclusive relationship between MDM2 alteration and TP53 inactivation (27). More importantly, our case carries MDM4 and DNMT3A co-mutation, which have not been reported in CRC by the Cbioportal Database.…”
Section: Discussionmentioning
confidence: 98%
“…Although none of these molecular alterations was found in CRC with HPD, which may be related to the low prevalence of MDM2/4 amplification (approximately 2%) and DNMT3A mutations (approximately 4%) in CRC. Suda et al ( 27 ) demonstrated that the principle of rare MDM4 amplification in CRC is unclear, which is different from the mechanism of a mutually exclusive relationship between MDM2 alteration and TP53 inactivation ( 27 ). More importantly, our case carries MDM4 and DNMT3A co-mutation, which have not been reported in CRC by the Cbioportal Database.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, the level of MDMX protein decreases in cases of gene amplification. 56 Therefore, the functional significance of MDMX is still unclear and needs further study. Unlike in hepatocellular carcinoma, TP53 mutation is not a common oncogenic driver in fibrolamellar hepatocellular carcinoma.…”
Section: Phosphorylationmentioning
confidence: 99%
“…The amplification and overexpression of MDMX in breast cancer have also been confirmed in Nottingham/Tenovus cohort with a well-characterized series of 990 cases and other studies and have been associated with p53 mutation, breast carcinogenesis, invasive disease, small tumor size, low grade, longer breast carcinoma specific survival (BCSS), and disease-free survival (DFS) ( 62 65 ). However, MDMX amplification is rare (1.4%) in colon cancer and its functional significance in this disease still needs further investigations ( 66 ). Mancini et al have found that the expression of full-length MDMX ( MDMX-FL ), but not its oncogenic MDMX-S variant is significantly associated with the responses of ovarian cancer patients to chemotherapy ( 67 ).…”
Section: Amplification and Overexpression Of Mdmx In Human Cancer Andmentioning
confidence: 99%